Les enseignants contractuels au Sénégal produit d'un nouvel ordre scolaire ou d'interactions internes au système éducatif ? - Aboubacar Abdulaye Barro
The power relations in the Senegalese school system show that local actors are the major stakeholders in it since 1995. Despite the continuing control of external funders, they play a key role in demands for higher salaries, the establishment of trade unions, and the re-ranking as "permanent" in the teaching profession, etc. The case of Senegal offers a perfect example for understanding the process of restructing educational systems in Francophone Africa. Senegal's open political sphere fosters the self-nomination of national actors. In addition, the standardization of models of schooling does not nullify the tensions between the local and the global.